1988
DOI: 10.7326/0003-4819-109-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Noninvasive Diagnosis of Pneumocystis carinii from Induced Liquefied Sputum

Abstract: Pneumocystis carinii organisms cluster in alveolar casts. A method for concentrating alveolar casts in sputum specimens might improve the diagnostic usefulness of sputum studies in possible cases of pulmonary infection with Pneumocystis carinii. The use of sputum induction to detect Pneumocystis carinii was studied in 40 consecutive patients with known or suspected human immunodeficiency virus infection having bronchoscopy for evaluation of pulmonary disease. Sputum produced by deep coughing induced by 3% sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 9 publications
0
31
0
1
Order By: Relevance
“…The remaining 36 articles were reviewed in detail, and 29 of these were excluded (see Appendix). Overall, data retrieved from seven publications were included in the meta-analysis [38][39][40][41][42][43][44]. Table 1 summarises the characteristics of the seven studies included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 36 articles were reviewed in detail, and 29 of these were excluded (see Appendix). Overall, data retrieved from seven publications were included in the meta-analysis [38][39][40][41][42][43][44]. Table 1 summarises the characteristics of the seven studies included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the organism is detectable on microscopic examination of induced sputum in 55-92% of PCP patients with HIV infection (39,40). In patients with PCP but without HIV infection, detectability is Ͻ10%; thus, bronchoalveolar lavage fluid examination is often required (38).…”
Section: Discussionmentioning
confidence: 99%
“…While colorimetric staining (e.g., Gomori methenamine silver nitrate, toluidine blue 0, and Giemsa stains) of expectorated sputum alone has a comparatively poor yield, several groups have found that the sensitivity of this procedure can be markedly increased when sputum specimens are obtained by hypertonic saline nebulization (2,33). Estimates of up to 55% sensitivity have been described using sputum induced by the nebulization technique, which can be further improved to 78% by addition of a sputum liquefication step using reducing agents such as dithiothreitol (47). Immunofluorescence staining of sputum specimens using monoclonal antibodies against surface antigens ofP.…”
Section: Diagnosismentioning
confidence: 99%